(untitled) (Canadian Medical Education Journal, 2022)
Background: Third-year enhanced skills programs, also known as family medicine (FM) PGY3 programs, have always been an area of debate. Their exponential growth does not stem from a strong body of academic evidence or public health needs assessment. This qualitative descriptive study explores the current perspectives of second-year FM residents at the University of Ottawa on extended training programs through semi-structured interviews. Results: Of the fifteen participants, eight were applying to PGY3 FM programs, six were not and one was unsure. Themes generated included: developing generalist niches within primary care, increasing confidence of FM graduates, allowing generalists to fill in healthcare gaps to meet community needs, meeting the pressures of workplace competition and employability requirements, and creating alternate paths to five-year specialties. 80% would extend their core FM training, with self-design and options of shorter time frames as preconditions. Conclusion: FM residents are interested in furthering their training, whether through extending core residency period or via enhanced skills programs. The demand for these programs will continue rising. Capitalizing on residents’ interests to catapult the profession forward and optimize the quality of healthcare should be the priority for licensing bodies and medical educators.